Um estudo sobre a deposição dos resíduos sólidos no município de Formosa do Oeste e a educação ambiental - Senkowski, Sabrina Thais Vieira Santos (2014)
The anthropic action has caused several environmental problems because man does not live in harmony with nature, but, explores and devastates, it, removing more than it can replenish, depositing more waste than it can absorb. Among the huge wave of environmental problems, this research has focused on the generation and disposal of solid waste as this theme is present in the context of several societies, including the city of Formosa do Oeste, where this work was done. For this, in the months of August and September 2014, a visit to the site where the waste collected is deposited in the city was held. Information was collected by means of closed questionnaires answered by students in the eighth grade at a public school in the city of Formosa do Oeste also performed an activity awareness in order to sensitize them about the importance of reducing the amount of waste generated, and recycling and reusing as much as possible of the waste generated. Data were analyzed using descriptive statistics and the results revealed that students although they know the destination of the waste generated in the county, mostly do not adhere practice to minimize the impacts of this, which is regrettable, because approximately 84% of the materials intended for landfill could be reused. According to the students who participated in the awareness of activity, it contributed to better know the problem caused by garbage and resulted in a change of intent on the part of respondents, indication that the objective was achieved.